Teachers' Motivational Strategies in Fostering Students' Motivation in English Learning - Rezkya Abdal; Sahril; Fitriyani (International Journal of Language, Education, and Literature, 2025)
Teaching English to high school students often faces challenges, as many students consider English difficult, leading to a lack of motivation to learn. Therefore, teachers need to employ appropriate motivational strategies to help students become more enthusiastic about learning. This study aims to explore the motivational strategies used by English teachers to enhance students’learning motivation at SMAN 3 Luwu Timur. This study used a descriptive qualitative approach, with two grade X English teachers as the subject. Data were collected through classroom observation and interviews. The findings show that among all the strategies used, two strategies dominate the teachers’practices: Creating Basic Motivational Conditions and Maintaining and Protecting Motivation. This indicates that the teachers rely on these strategies as part of their main approach to enhancing students’ motivation in learning. This research provides an overview of the importance of teachers’motovational startegies in creating a more enjoyable and effective English learning environment.